2017
DOI: 10.1080/14767058.2017.1373760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of agreement of placental growth factor (PlGF) tests and the soluble FMS-like tyrosine kinase 1 (sFlt-1)/PlGF ratio, comparison of predictive accuracy for pre-eclampsia, and relation to uterine artery Doppler and response to aspirin

Abstract: There was good agreement between PlGF tests and limited agreement between PlGF tests and the sFlt-1/PlGF ratio. All tests have heightened predictive accuracy for preterm pre-eclampsia. Abnormal PlGF or sFlt-1/PlGF ratio relates to abnormal uterine artery Doppler but not platelet response to aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The interpretation of this finding according to the investigators was that aspirin could be efficacious through other pathways other than altering the levels of angiogenic factors [86]. Another recent study did not find an association between every form of adherence to aspirin therapy and abnormal angiogenic markers [87]. Therefore, future studies are required to further investigate the effect of aspirin on circulating levels of angiogenic factors in different racial/population groups.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of this finding according to the investigators was that aspirin could be efficacious through other pathways other than altering the levels of angiogenic factors [86]. Another recent study did not find an association between every form of adherence to aspirin therapy and abnormal angiogenic markers [87]. Therefore, future studies are required to further investigate the effect of aspirin on circulating levels of angiogenic factors in different racial/population groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that overexpression of sFlt-1 induces a preeclampsia–like phenotype, which includes increased BP, proteinuria, and endothelial dysfunction ( Caillon et al 2018 ). Also, it has been demonstrated that increased sFlt-1 will lead to a more severe preeclampsia-like phenotype in eNOS −/− mice ( Navaratnam et al 2017 ). Symptoms including the increase of UAE, the decrease of CCr, and more severe endotheliosis are aggravated by a synergistic effect combining the overexpression of sFlt-1 and the depletion of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Results of longitudinal study conducted by Porto and coworkers indicated that all pregnancies complicated with early onset of preeclampsia have had significantly higher uterine artery PI between 16+0 and 19+6 weeks of gestation (26). Navaratnam and colleagues went a step further, and compared PlGF tests and the sFlt-1/PlGF ratio with abnormal uterine artery Doppler (27). Results of their investigation showed significant association between PlGF or sFlt-1/PlGF ratio with results of Doppler parameters.…”
Section: Uterine Artery Doppler In Preeclampsia Predictionmentioning
confidence: 99%